Biosynthesis of L-Lysine-a-Oxidase, an Antitumor Enzyme, by Trichoderma spp - I. P. Smirnova; S. B. Alekseev; A. A. Shevchenko (Антибиотики и Химиотерапия, 2020)
Strains of Trichoderma spp., producing L-lysine-a-oxidase, prospective in chemotherapy of malignant tumors, were studied. The best results of the enzyme biosynthesis were observed on the wheat bran medium. When grown on the media with various pH levels, the strains showed different spectra of the L-aminooxidase activity. The highest activity of the strains was recorded with respect to destruction of L-lysine. The lysine-producing organism Brevibacterium sp. induced L-lysine-a-oxidase activity in Trichoderma spp.